Detection of Fire and its Control using Arduino and Proteus - Vernekar, Harsha Govindray (Journal of Electronics and Informatics, 2023)
Fire detection systems have been typically developed to detect fire and alert people to vacate that particular location. However, this research involves the design and development of a system for the detection and control of fire. To detect fire, temperature and smoke sensors are used. This proposed work is executed using Arduino and Proteus software. To control the working of sensors at the transmitter part, Arduino Uno is used. DC motor which is used as the controller, rotates upon the detection of over temperature and excess smoke, and then the alert signal is produced. In future, this DC motor can be replaced with a pump which would aid in controlling the fire.